Bone regeneration in cranioplasty and clinical complications in rabbits with alloxan-induced diabetes - Vieira, Evanice Menezes Marçal [UNESP]; Ueno, Camila Satie Ferreira [UNESP]; Valva, Vivian Neves [UNESP]; Goulart, Maria das Graças Vilela [UNESP]; Nogueira, Terezinha de Oliveira [UNESP]; Gomes, Mônica Fernandes [UNESP] (FapUNIFESP (SciELO), 2008)
This research evaluated the bone repair process in surgical defects created on the parietal bones of diabetic rabbits using the guided bone regeneration technique to observe the effects of alloxan in the induction of diabetes mellitus. Twenty-four adult rabbits were divided into three study groups: control (C), diabetic (D) and diabetic associated to polytetrafluoroethylene (PTFE) membrane (D-PTFE). For diabetes induction the animals received one dose of monohydrated alloxan (90 mg/kg) by intravenous administration in the auricular or femoral vein. In group D-PTFE the membrane covered both the floor and the surface of the bone defect. In groups D and C, the bone defect was filled up with blood clot. The specimens were fixed in 10% formol and prepared for histomorphometric analysis. The results showed that the 90 mg/kg dose of monohydrate alloxan was sufficient to promote diabetes mellitus when administered in the auricular vein. Bone regeneration was slower in the diabetic group when compared with the control and diabetic-PTFE groups, but there was no significant statistical difference between the two experimental groups (D and D-PTFE). The oral and general clinical complications among the diabetics were weight loss, polyuria, polyphagia and severe chronic gingivitis.
Keywords: Alloxan; Bone regeneration; Diabetes complications; Diabetes mellitus; alloxan; biomaterial; politef; analysis of variance; animal; bone regeneration; chemically induced disorder; disease model; drug effect; experimental diabetes mellitus; pancreas; pathophysiology; physiology; rabbit; randomization; skull; wound healing; Analysis of Variance; Animals; Biocompatible Materials; Bone Regeneration; Diabetes Mellitus, Experimental; Disease Models, Animal; Pancreas; Parietal Bone; Polytetrafluoroethylene; Rabbits; Random Allocation; Skull; Wound Healing